Coupling of chromatography with surface-enhanced Raman spectroscopy: trends and prospects - Dmitrieva, Ekaterina V.; Kapitanova, Olesya O.; Lv, Shixian; Sinyashin, Oleg G.; Veselova, Irina A. (Frontiers in Chemistry, 2025)
Surface-enhanced Raman spectroscopy is a powerful analytical technique for the determination of analytes with the advantages of sensitivity, portability, and simplicity, able to provide structural information for the identification of compounds. However, when it comes to the analysis of complex samples, matrix components may interfere with the analyte quantification. To overcome this shortcoming, a number of approaches have been proposed, such as extraction techniques. Among them, the coupling of chromatography with surface-enhanced Raman spectroscopy seems to be promising. It allows combining the advantages of both techniques, i.e., high efficiency of chromatographic separation and high sensitivity of surface enhanced Raman scattering detection, and makes possible simultaneous quantification of multiple analytes. The review summarizes the latest achievements in the combination of these techniques.